Pengaruh Efektivitas Iklan Televisi Dan Citra Merek Terhadap Keputusan Konsumen Membeli Sepeda Motor Honda Di Langkat Sumatera Utara - Kalsum, Eka Umi; Siregar, Roswani (Mahesa Research Center, 2023)
This study describes the effectiveness of television advertising and brand image on purchasing decisions for Honda motorcycles in Langkat, North Sumatra. The theory used in this study includes the theory of advertising effectiveness, brand image and purchasing decisions. The population in this study were 61 Honda motorbike users who crossed the village of Tanjung Gunung Langkat, North Sumatra. The data analysis model used is multiple linear regression analysis. The research method uses a quantitative descriptive approach supported by a survey, and is explanatory in nature. The results of the research by testing the t-test hypothesis show that the effectiveness of television advertising has a positive and significant effect on purchasing decisions for Honda motorbikes in Langkat, North Sumatra. Brand image has a positive and significant effect on purchasing decisions for Honda motorcycles in North Sumatra. The results of the F test show that the effectiveness of television advertising and brand image have a positive and significant effect on the decision to purchase Honda motorcycles in North Sumatra. The coefficient of determination (R2) for the effectiveness of television advertising and brand image is able to explain the purchasing decision variable by 88.1% and the remaining 11.9% is influenced by other variables not examined in this study such as product quality, service, and so on.